Oxford–AstraZeneca COVID-19 vaccine: need of a reasoned and effective vaccine campaign. (July 2021) - Vallée, A.; Chan-Hew-Wai, A.; Bonan, B.; Lesprit, P.; Parquin, F.; Catherinot, É.; Choucair, J.; Billard, D.; Amiel-Taieb, C.; Camps, È.; Cerf, C.; Zucman, D.; et al.
Abstract: Objectives: A strong COVID-19 vaccine campaign is needed to reach the herd immunity and reduce this pandemic infection. Study design: In the Foch Hospital, France, in February 2021, 451 healthcare workers were vaccinated by a first dose of AstraZeneca vaccine. Methods: Adverse effects were reported to our pharmaco-vigilance circuit, by an online and anonymous questionnaire following the first weeks of the vaccinal campaign to healthcare workers. Results: Two hundred seventy-four (60.8%) of them reported multiple adverse effects. Main adverse effects reported were feverish state/chills (65.7%), fatigue/physical discomfort (62.4%), arthralgia/muscle pain (61.0%) and fever (44.5%). Conclusions: On March 2021 many European countries suspended AstraZeneca vaccine for one week due to safety uncertainty. Thus, confidence in its efficacy is undermined. However, the benefit/risk balance is clearly in favor of vaccination.